Physical and thermochemical characterisation of Malaysian biomass ashes - Wan Azlina, Wan Ab Karim Ghani, Dr.; Mohd Syafik Firdaus, Abdullah; Khamirul Amin, Matori, Dr.; Azil Bahari, Alias; da Silva, Gabriel, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/